Portrait of Pedagogical Content Knowledge (PCK) of Science Teachers in Global Islamic Boarding School Material Classification of Living Things - Putri Hasanah; Fahmi; Yudha Irhasyuarna; Rizky Febriyani Putri (Postgraduate, University of Mataram, 2024)
Pedagogical Content Knowledge (PCK) is a wedge between Content Knowledge and Pedagogical Knowledge, namely knowledge about the material being taught and how to teach it. The teacher's ability to understand the material and manage learning greatly determines the improvement of the quality of learning in the classroom in realizing meaningful learning for students. This study aims to describe the Pedagogical Content Knowledge (PCK) for science teachers at the Global Islamic Boarding School Middle School (GIBS) regarding the classification of living things. This type of research is descriptive qualitative. Data collection techniques using observation sheets, interviews and documentation. The results of the study show that teachers can balance between two competencies, namely knowledge of material classification of living things and how to teach it using 7 aspects of Pedagogical Content Knowledge (PCK), namely Content Knowledge, Knowledge of Specific Context, Knowledge of Learners and Learning, Pedagogical Knowledge, Curriculum Knowledge, Knowledge of General Education Context, Assessment Procedures, Evaluation of Outcomes – Educational Ends, Goals, Purposes, and Values.